DEGRADATION OF REACTIVE DYES USING IMMOBILIZED PEROXIDASE PURIFIED FROM NIGELLA SATIVA - Aziz, G. M.; Hussein, S. I.; Abbass, S. D.; Ibrahim, A. L.; Abbas, D. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The goal of the current work was to use Nigella sativa seeds' free and immobilised peroxidase to degrade textile dyes that pollute the environment and water. The enzyme was extracted for 15 minutes using a 1:20 (w:v) ratio, sodium acetate buffer at 0.2 M, and pH 5.0 after the optimal conditions for extracting the enzyme from Nigella seeds were determined. This yielded the highest specific activity of the enzyme, 1750 units/mg protein. The enzyme was purified in two stages: sucrose concentration and Sephadex G-150 gel filtration. With a 35% enzyme yield, the findings demonstrated a 2,8-fold increase in final purification folds. The entrapment method with Ca alginate was used to immobilise peroxidase, and the immobilisation ratio was 49%. Under optimum circumstances, pH 5, temperature 37oC after 3 hours with textile dyes such as yellow, red, black, and blue dyes, the removal efficacy of dyes by crude enzyme (free, immobilized) and partially purified peroxidase were tested. With crude peroxidase, dye removal efficiency peaked at (76.9, 88.7, 91, and 88) %, respectively. The efficiency of the crude immobilised enzyme in removing the four dyes was roughly equivalent to the efficiency of the purified enzyme (70, 81, 72, and 56.4%, respectively).